Baby Boom or Bust? the New Media Effect on Political Participation. Issue 1 (2nd January 2018) - Towner, Terri L.; Muñoz, Caroline Lego
ABSTRACT: A considerable number of studies have investigated the influence of new media on political attitudes and behaviors. However, much of this research focuses on young people, ignoring other age cohorts, particularly Baby Boomers (born between 1946 and 1964). To fill this gap, this research examines the influence of attention to specific forms of traditional and online media on Baby Boomers' online and offline political participation during the fall 2012 U.S. presidential campaign. Drawing on a Baby Boomer survey panel, responses were collected during the 2012 general election to analyze the empirical relationship between attention to traditional and online media sources and political participation. Data analyses reveal that Boomers' attention to traditional media sources, particularly television, did not increase their offline and online political participation. Instead, various forms of offline and online participation were consistently heightened by Boomers' attention to presidential candidate websites. In addition, attention to Facebook for campaign information was positively linked to online engagement. Boomers' attention to blogs, Twitter, and YouTube were associated with only certain types of online and offline activities.